Optimizing the Role of Waqf in Sustainable Development through an Islamic Education Perspective: A Comprehensive Literature Study - Siregar, Kardina Engelina (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2024)
The role of waqf (Islamic endowment) in fostering sustainable development has garnered increasing attention in recent years. This study aims to explore the optimization of waqf in sustainable development through the lens of Islamic education. Utilizing a comprehensive literature review methodology, this research synthesizes findings from various academic sources, including journal articles, books, and reports, to understand the multifaceted contributions of waqf. The study highlights the historical significance of waqf in socio-economic development and examines contemporary practices and challenges. It emphasizes the potential of Islamic education in enhancing the awareness, management, and strategic utilization of waqf assets. The findings suggest that integrating Islamic educational principles with modern developmental strategies can significantly enhance the efficacy of waqf in addressing current socio-economic issues. This research offers valuable insights for policymakers, educators, and stakeholders in the waqf sector, advocating for a more structured and informed approach to leverage waqf for sustainable development.